Nostalgia and Stories of Early Arrival Amongst the Turkish Diaspora in Broadmeadows - Orhan Karagoz (Turkish Journal of Diaspora Studies, 2024)
This article discusses how Turkish people in the suburb of Broadmeadows in Melbourne, Australia, construct nostalgia for their earlier days as migrants. Furthermore, it highlights the didactic and ethical role this nostalgia plays within the Turkish community. Turkish migrants began to manifest nostalgia for the earlier days in Australia after the dream of returning to the homeland began to wane. This nostalgia presents an image of the ideal Turk to the younger generations in Australia and therefore helps to preserve the Turkish identity. This nostalgia also enables Turks to distance themselves from negative images of the contemporary homeland, allowing them to present themselves as authentic Turks; it also helps Turkish Australians to cope with their economic marginality in Australia. Nostalgia for the early days in Australia therefore has many purposes for Turkish Australians today.